Sustainable Nations: What do Aggregate Indicators tell us? - J. Ram Pillarisetti; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2008)
What is a 'sustainable nation' and how can we identify and rank `sustainable nations'? Are nations producing and consuming in a sustainable way? Aggregate indicators have been proposed to answer these questions. This paper quantitatively compares three aggregate indicators of sustainability: the World Bank's `Genuine Savings' measure, the `Ecological Footprint' and the `Environmental Sustainability Index'. It is concluded that rankings of sustainable nations vary significantly among these indicators. Implications of this disagreement for analysis and policy are suggested.
Keywords: O1; Q2; Q28; F0; 330; Adjusted Net Savings; Ecological Debt; Ecological Footprint; Environmental Sustainability Index; Genuine Savings; Sustainability; Nachhaltige Entwicklung; Umweltbelastung; Messung; Entwicklungsindikator; Welt